Analysis of User Satisfaction of Telemedicine Services During COVID-19 Self-Isolation among FPH Students at the Universitas Indonesia - Mulyaningrum, Fathiya Nissa; Raihanny, Nadya (UI Scholars Hub, 2024)
Telemedicine has become a new paradigm in the world of health since its popular use to assist the Ministry of Health in monitoring self-isolating patients during the COVID-19 pandemic. This study aims to analyze service quality variables related to user satisfaction with telemedicine services during COVID-19 self-isolation among students in FPH UI. This research is quantitative research with a cross-sectional approach. The results show that the platform most widely used for telemedicine services during the COVID-19 pandemic was platform H by 25 people. The average satisfaction of telemedicine users during self-isolation tends to be high, namely 3.8 with the lowest value being 2.3 (SD=0.534). Service quality and user satisfaction are all positively correlated with weak to strong correlation levels, namely responsiveness (r=0.306), service reliability (r=0.598), information quality (r=0.490), empathy (r=0.509), ease of service (r=0.633), perceived usefulness (r=0.486). The quality improvement factor is based on high satisfaction in easier appointment registration, savings in out-of-pocket costs for travel and queuing time at health services. However, holistic health and regulatory services are needed to address user data security threats.